Seni Dalam Persfektif Hadist (Kajian Ma`ani Persfektif Muhammadiyah) - Ahmad Rifai (LPPAIK Universitas Muhammadiyah Bandung, 2021)
The law of art in Islam is hotly told on social media, Calls for the illegality of art echo on social media. Muhammadiyah began to pursue art by opening an art and design program at the muhammadiyah university, including at the University of Muhammadiyah Bandung. This is interesting to study, to find out the purpose of Muhammadiyah in opening an art program when the call for illegal art to go viral on social media. The purpose of this study is to find out the principles and laws of art in Muhammadiyah. This research method uses qualitative research by examining hadith about art. The hadith approach used is the science of riwayah hadith and the science of ma'ani hadith. In conclusion, there is a hadith that forbids images and statues, there is a hadith that allows making dolls for toys, draw clothes, and draw lifeless creatures. The law of art in Muhammadiyah is allowed if it is closer to monotheism and benefit. the law of art is forbidden if it leads to polytheism.